AZITHROMYCIN AND OSELTAMIVIR QUANTIFICATION METHOD DEVELOPED AND VALIDATED USING LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY IN DRIED BLOOD SPOT - RAHMANIA, TESIA AISYAH; HARAHAP, YAHDIANA; SANDY, KURNIA (International Journal of Applied Pharmaceutics, 2024)
Objective: The development and use of bio-sampling techniques for the analysis of COVID-19 drugs oseltamivir and azithromycin using the Dried Blood Spot technique simultaneously using LC-MS/MS aims to obtain optimal conditions and validated analytical methods using LC-MS/MS according to Food and Drug Administration 2018 recommendations. Methods: Azithromycin and oseltamivir analyses were performed using LC-MS/MS with C18 Acquity® Bridged Ethylene Hybrid (BEH) column 1.7 m, 100 x 2.1 mm. The matrix sample used is Dried Blood Spot (DBS) with azithromycin and Oseltamivir as the raw material and acyclovir as the internal standard. Optimum analytical conditions were obtained on a gradient mobile phase using 0.1% formic acid-methanol solution with a flow rate of 0.2 ml/minute. The quantification of the analysis was carried out using triple quadrupole mass spectrometry with positive electrospray ionization (ESI) mode. Results: The calibration curve ranged from 0.5 to 160 g/ml, and the Lower Limit of Quantification (LLOQ) achieved was 25.31 and 25.37 ng/ml. Sensitivity, selectivity, linearity, precision, carry-over, accuracy, stability, and recovery were found to be within the suitable limits and fully validated by the guidelines from the Food and Drug Administration 2018. Conclusion: The method developed successfully passed all of the FDA's 2018 full validation guidelines, with the LLOQ achieved for azithromycin and Oseltamivir was 25.31 and 25.37 ng/ml.